The role of the people in the internal and external relataions in Andalusia238- 366H/852-976AD - Karhili , . Nabeel (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research deals with the role of the people in the interior and relations within Andalusia in order to understand what these relations are. It is necessary to understand what this community is and their location within the Andalusia Muslim community. There was talk of holding the people of Dhmmah as the leyal framework that determines the conditions far there residence within the Islamic state. Through reference the relationship between the Islamic state and non-Muslim citizens can be indentified and established. The Jews and Christians manged to live adecend life and the state allowed them to established their lives without interfering in their own affairs. They were given the freedom to choose whose would run their judicial of fairs and practice their religious rites. After explaning their internat political situation, the external role was addressed to them.through the embassies of Andalusia to neigh boring countries and this role played by both Jews and Christians alike. It is up their foreign sensblilities snd their knowledge of the mentality of Europeen countries and their mastery of the lamguages that allowed them to easly communicate.